Analisis Pemikiran John Wesley Terhadap Kekudusan Hidup dan Predestinasi Berdasarkan Teologi Reformasi. - Riky Handoko Sitindaon; Putri Rosinta Lestari (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2022)
The holiness of life is a continuation of the process of the person who is born again. A person who has been born again is a person who has been sanctified by God. In the process of sanctification, the sinful man has no share in sanctifying himself. The holiness of life and predestination are in the authority of God, therefore humans have no share in determining salvation and self-sanctification. Since then Allah has determined everything and no human being knows what Allah has determined. Therefore God offers Grace to all people through His Son, the Lord Jesus, so that everyone who receives it can be saved. Predestination is an understanding that makes it easier for everyone to understand God's sovereignty in choosing and saving. Holiness in life is God's process in the person who has been chosen and saved to always live a godly life. Both are God's works in human life and prove that God is sovereign.